Mental health in retired professional football players: 12-month incidence, adverse life events and support. (January 2017) - van Ramele, Serena; Aoki, Haruhito; Kerkhoffs, Gino M.M.J.; Gouttebarge, Vincent
Abstract: Objectives: The primary aim was to explore the incidence of symptoms of common mental disorders (CMD; distress, sleep disturbance, anxiety/depression, adverse alcohol use) in retired professional football players and to explore the association between adverse life events and the onset of symptoms of CMD. The secondary aim was to get an insight into the views and needs of retired professional football players on medical support related to symptoms of CMD. Design: An observational prospective cohort study with three measurements over a follow-up period of twelve months was conducted among retired professional football players. Method: The data for symptoms of CMD and adverse life events was collected by using validated questionnaires. The views and needs were explored by means of five questions. Results: The 12-month incidence of symptoms of CMD (self-reported and not clinically diagnosed) ranged from 11 to 29%. Retired professional football players with one or two life events were 1.7 times more likely to report distress than retired football players with no life events. The risk with three or more recent life events on sleep disturbance was more than 4.5 times higher than with no recent life events. Conclusions: The 12-months incidence of symptoms of CMD in retired professional football players seems high compared to the general population. More life events showed a higher risk of experiencing distress and sleep disturbance in retired professional football players. The views and needs showed that there is a need for support for current and former professional football players. Highlights: The 12-month incidence of symptoms of CMD ranged from 11 to 29%. More life events showed a higher risk of experiencing distress and sleep disturbance in retired professional football players. Our study showed that there is a need for support for current and former professional football players.